FONOLOGICAL SYSTEM OF THE RONGKONG TAE DIALECT REGENCY NORTH LUWU - Runimeirati (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims to identify and describe qualitatively the phonological system of Tae Rongkong dialect in North Luwu Regency, South Sulawesi. The analysis was carried out on 200 Swades vocabularies carried out in the field. The results of the study were analyzed in four categories. The categories in question are phoneme identification, phoneme distribution, phoneme clusters and tribal patterns in the Tae Rongkong dialect. Based on phoneme identification, there were 5 (five) vowel phonemes [u], [a], [e], [O], and [o]; 9 (Nine) consonant phonemes [m], [l], [s], [r], [b], [k], [d], [t], and [n]; based on the distribution of vowel phonemes found 9 (nine) vowel phonemes [a], [i], [u], [I], [e], [e], [o], [U], and [O]; while the distribution of consonant phonemes found 15 (fifteen) consonant phonemes [b], [d], [g], [j], [k], [l], [m], [n], [ŋ], [ p], [r], [s], [t], [v], and [?]; also found 10 (ten) vocal phoneme clusters /ai/, /au/, /ae/, /ia/, /ua/, /uo/, /ei/, /oe/, /oa/, and /io/; and in the consonant phoneme group, 6 (six) consonant phonemes were found /nd/, /nt/, /mb/, /mp/, /ŋk/, /kg/, and /nd/; The tribal patterns found by researchers in the Tae Rongkong dialect consist of trisyllabic patterns with monosyllabic V, polysyllabic K.V, V.K, trisyllabic K.K.KV and four-syllabic KK.K.K.V.